2012
DOI: 10.1007/s12199-012-0273-y
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous changes in high-fat and high-cholesterol diet-induced steatohepatitis and severe fibrosis and those underlying molecular mechanisms in novel SHRSP5/Dmcr rat

Abstract: Objectives The aim of this study was to identify the molecular mechanisms underlying high-fat and high-cholesterol (HFC) diet-induced steatohepatitis and associated liver fibrosis progression in a novel stroke-prone, spontaneously hypertensive 5/Dmcr (SHRSP5/Dmcr) rat model. Methods SHRSP5/Dmcr rats were given the control or HFC-diet for 2, 8, and 16 weeks. Plasma and hepatic gene expression of key molecules involved in fatty acid oxidation, inflammation, oxidative stress, and fibrosis were subsequently analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…SOD also plays important roles in antioxidant defense by catalyzing the dismutation of superoxide anions [22]. In our previous study, we demonstrated that the HFC diet decreased the hepatic level of SOD1 in the hypertensive SHRSP5/Dmcr strain [39]. In the present study, we also found that SOD2 expression was suppressed by the HFC diet in the livers of SHRSP5/Dmcr rats but not in those of the WKY and SHR rats.…”
Section: Discussionsupporting
confidence: 68%
“…SOD also plays important roles in antioxidant defense by catalyzing the dismutation of superoxide anions [22]. In our previous study, we demonstrated that the HFC diet decreased the hepatic level of SOD1 in the hypertensive SHRSP5/Dmcr strain [39]. In the present study, we also found that SOD2 expression was suppressed by the HFC diet in the livers of SHRSP5/Dmcr rats but not in those of the WKY and SHR rats.…”
Section: Discussionsupporting
confidence: 68%
“…This model recapitulated histological features of human NASH and exhibited a similar physiological condition to a subgroup of NASH patients without obesity or insulin resistance. In view of the extraordinary cholesterol content (5 % by weight) in the HFC diet, and the hepatic total cholesterol which progressively accumulated as liver disease developed, unlike triglycerides [9, 10], the accumulation of cholesterol, rather than triglycerides, may have played a critical role in the progression of fibrotic steatohepatitis in this dietary rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that HFC feeding significantly induces the hepatic profibrogenic proteins TGF-β1 and α-SMA in SHRSP5/Dmcr male rats [25]. Herein, the HFC diet increased hepatic TGF-β1 and α-SMA protein expression levels similarly in both genders at 8 and 14 weeks.…”
Section: Gender Differences In Fibrogenic Indicesmentioning
confidence: 60%